Qualifications and Safety Culture of the OSH Climate Effect of Service of Occupational Health and Safety Services in Turkey, Wavin Pilsa Example (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2019)
In modern occupational health and safety approach, determining sources of hazards and risks in working environment, taking prevention and protection measures and informing employees are important basic issues. Every year 313 million non-fatal accident occurs. Considering economic situations, it is estimated that countries are loosing almost over 4% of gross domestic product because of occupational accidents and deseases. Occupational Health and Safety Law, legislated in 2012, has brought new orders to working life. The by-laws related to the articles of this law have brought important responsibilities to employers and employees. A healty and safe working environment is as much important for protecting right of life which is one of the primer human rights as for quality, productivity, sustainability and establishing working peace. Occupational health and safety is a culture. In working environment, changing working culture is chalenging. To achieve this changing goal, employers and autherised personnel have important responsibilities. The security climate is widely recognized as an important organizational factor in securing workplace safety. Various definitions have been made for security climate. A climate of security can be defined as an organization / organization / organization / organization, in short, as a concrete measure of employees' perceptions and attitudes that reflect their beliefs about security in a work environment. In this study, the effect of the security climate in a workplace on OHS services was examinedsecurity culture